Penanaman Kembali Hutan Mangrove Sebagai Upaya Pelestarian Lingkungan Pada Kebun Raya Mangrove Gunung Anyar Surabaya - Sri Anggraini Kusuma Dewi; Mohammad Roesli; M. Hidayat; Sumarso; Supolo Setyo Wibowo; Bastianto Nugroho; Asep Heri; Priambodo Adi Wibowo; Gesang Iswahyudi (Universitas Merdeka Surabaya, 2022)
The Gunung Anyar Mangrove Botanical Garden is located on Jalan Medokan Sawah Timur, Segoro Tambak Sedati, Medokan Ayu, Rungkut District, Surabaya City, East Java. The area which has an area of 25 hectares is known as a place for nature conservation, equipped with various supporting facilities, such as a pavilion, fishing pond and jogging track. Various types of mangrove plants and various kinds of wildlife such as long-tailed monkeys, bird species and other animals also provide added value. In its development this area also functions as a tourist place, a means of education and gain knowledge. To maximize its function, this conservation area needs to be continuously maintained, including by replanting mangrove forests. This community service activity aims to support efforts to rehabilitate and improve mangrove ecosystems, increase the participation of the community, local government, and universities in the action of saving the coast in the mangrove botanical garden area of Gunung Anyar Surabaya.